A New-World Model of Female Epistolarity: The Correspondence of Marie de L'incarnation - Zecher, Carla (Studies in Canadian Literature, 1996)
Marie de l'Incarnation's Correspondence comprises the missives of a Touraine bourgeoise widow, mother, tradeswoman, mystic, and missionary educator. The unique circumstances of Marie's letters - the fact that her son became her editor - problematizes the distinction between male lettres and female ignorants that typically guided seventeenth-century thinking with regard to women's epistolary writing.